Hierarchical Value Chains Encompassing Freight Transportation and Logistics Sectors in the United States: Network Analysis Approach. Issue 1 (January 2017) - Mesa-Arango, Rodrigo; Kumar, Indraneel
This research reveals value chain (VC) clusters in which freight transportation modes (i.e., truck, rail, air, water, and pipelines), freight supporting activities (i.e., couriers and messengers and warehousing and storage), and other industry sectors have strong economic inter-dependencies. The most recent input–output data in the United States were used to construct the 2014 direct requirements matrix and generate a network of economic interdependencies between industry sectors. Community detection, a complex network analysis method, was used to reveal the Corresponding VCs in the economic network. A novel procedure uncovered hierarchical VC communities (VCCs) for each freight transportation and logistics sector. Thus, seven distinctive VCCs with unique underlying activities were found. In general, freight industries are hierarchically clustered to VCCs related to raw materials; services; metals; agriculture; textile, apparel, and paper; wood products; and others. Results are important for the areas of transportation economics, regional economic development, competitiveness, and multimodal freight transportation.